Physical, Mechanical and Chemical Properties of Dewatered Sewage Sludge and Red Gypsum Mix as a Potential Recycling Product - Nor Azalina, Rosli; Hamidi, Abdul Aziz; Mohamad Razip, Selamat; Leonard Lik Pueh, Lim (Trans Tech Publications Ltd., 2019)
This paper aims to present the characteristic of dewatered sewage sludge (SS) and red gypsum (RG) to determine their recycling potentials into a valuable product. The materials were characterized based on their physical-mechanical-chemical properties and morphology. The results showed that dewatered sewage sludge and red gypsum could complement each other when used together to form a new material the merits of which will be investigated in subsequent studies. RG has a better performance in term of plasticity and strength than SS due to fines content in the former and therefore its ability to retain moisture that contributes to cohesion between particles. Fine prisms and closer packing particles add strength in RG leading to higher resistance in compression. Unlike RG, SS has coarser particle and more voids causing it to lose the moisture content and becomes easily disintegrated. Chemical compositions of RG and SS as determined by XRF demonstrated a significant amount of CaO in the former and SiO2 in the latter; the formation of hydrated products in the form of CSH and CAH gel from hydration or pozzolanic reaction contributes to strength improvement of the SS.